Maslahah Value Inference in the Application of Accrual-Based Accounting on Regional Government - Jamaluddin Majid; Ambo Asse; Syaripuddin Rasyid; Safri Haliding; Bustan Ramli (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2023)
The primary objective of this study is to promote the incorporation of Maslahah values within the framework of accrual-based accounting practices in local government entities. This research employs a qualitative approach with a phenomenological perspective, drawing data partially from extensive literature reviews. The findings of this research emphasize the pivotal role of values when implementing accrual-based accounting in local governments. A critical aspect revolves around the ability to enforce regulations and codes of ethics within these governmental bodies. This enforcement, in turn, facilitates the production of financial reports that are not only accurate but also transparent and accountable. Furthermore, the adoption of accrual-based accounting should be coupled with the application of Maslahah values within the society. Values like honesty, accountability, fairness, and prosperity should underpin the financial practices of local governments. By doing so, leaders, who are key stakeholders, can be held accountable not only to their constituents but also in alignment with their moral and ethical obligations to a higher authority. In conclusion, this study underscores the importance of merging accounting practices with ethical values, ultimately benefiting local governments and the broader society they serve.